2020
DOI: 10.5433/1679-0359.2020v41n5supl1p1897
|View full text |Cite
|
Sign up to set email alerts
|

Morphophysiology of yellow passion fruit seedlings under application of nitrogen and potassium and irrigation with high-salinity water

Abstract: Salinity is one of the most problematic abiotic stresses in agriculture globally, especially in semi-arid regions. Thus, the application of nutrients, such as nitrogen and potassium to improve plant nutritional conditions may be a viable alternative to minimize the negative effects of saline stress. Therefore, the aim of this study was to evaluate the morphophysiological behavior of yellow passion fruit seedlings under varying nitrogen and potassium doses and irrigation with salt water. The experimental design… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 24 publications
1
8
0
Order By: Relevance
“…In the soil without mulching, irrigation with high-salinity water increased the WUE from 3.98 to 4.75 mmol CO 2 mol -1 H 2 O in yellow passion fruit propagated by seeds and from 2.53 to 4.88 mmol CO 2 mol -1 CO 2 in yellow passion fruit grafted on P. cincinnata, representing increments of 19.3 and 92.9%, respectively (Figure 3B). These results corroborate those observed by Figueiredo et al (2020), who found that the yellow passion fruit plant irrigated with saline water increased its WUE, leading to the conclusion that the crop has a certain tolerance to salt stress due to the maintenance, to a certain extent, of carbon assimilation.…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…In the soil without mulching, irrigation with high-salinity water increased the WUE from 3.98 to 4.75 mmol CO 2 mol -1 H 2 O in yellow passion fruit propagated by seeds and from 2.53 to 4.88 mmol CO 2 mol -1 CO 2 in yellow passion fruit grafted on P. cincinnata, representing increments of 19.3 and 92.9%, respectively (Figure 3B). These results corroborate those observed by Figueiredo et al (2020), who found that the yellow passion fruit plant irrigated with saline water increased its WUE, leading to the conclusion that the crop has a certain tolerance to salt stress due to the maintenance, to a certain extent, of carbon assimilation.…”
Section: Resultssupporting
confidence: 91%
“…Yellow passion fruit (Passiflora edulis f. flavicarpa Deneger) is an economically important fruit for Brazil and especially for the Northeast region, where 71.2% of Brazilian passion fruit was harvested in 2020 (IBGE, 2021). In this region, the soil and climate conditions are favorable to the exploitation of the crop, with the exception of rain (Figueiredo et al, 2020), so irrigation is required, and the available water sources naturally contain high levels of soluble salts (Moura et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Saline stress affects the accumulation of phytomass, limiting the absorption of water and essential nutrients, with immediate effects on cell growth and expansion (Nóbrega et al, 2022). Figueiredo et al (2020) observed the influence of high salinity on dry phytomass in passion fruit plants.…”
Section: Discussionmentioning
confidence: 99%
“…Based on this context, the increase in LMR observed in this work can be explained by the greater fraction of material retained in the leaves, i.e., the lower export of photoassimilates from the leaves to the other parts of the plant (Silva et al, 2021). The increase in LMR under increasing levels of saline water was described by Silva et al (2023) for Ocimum basilicum L., and under doses of nitrogen and potassium by Figueiredo et al (2020) for Passiflora edulis.…”
Section: Discussionmentioning
confidence: 99%